PENGAWETAN TIGA JENIS BAMBU DENGAN METODE RENDAMAN DINGIN - Barly Barly; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Cold soaking tests of three bamboo species in Formula 7 preservative were performed. Results indicated that cold soaking in one day with 5% Formula 7 gives satisfactory penetration and retention in the specimens of betung and andong species. The specimens of tali species gave satisfactory results when treated in three days.